Stormwater Assessment and Management Using Gis Modelling in The Urban Catchment of Port Harcourt, Nigeria - NSIEGBE, Dickson Kinikawo; WELI, Vincent E; CHUKWU-OKEAH, Gift O; NSIEGBE, Dickson Kinikawo (Zien Journals, 2022)
The management of storm water is a significant challenge in several urban areas in Nigeria. Urban areas often times have local flooding as storm water is channelled along streets as runoff may not be able to escape from the environment and may cause flooding (Bryan 2002). Thus, the period of heavy rains is known in Nigerian cities for flooding and associated damages The sustainable technique which is appropriate for storm water harvesting is from point source, water management and purification (treatment), this can make urban environments to be self-sustaining in terms of water resources. The study seeks to assess stormwater generation and management which involves the hard and soft engineering projects which involves the construction, operation, and maintenance approaches which includes dams, artificial levees, and channel straightening. The study adopted the correlational research design were data were analysed using hydrological modelling techniques using GIS to achieve the study objective. Thus a model to show the stormwater generation was done weighing and overlaying the DEM data in the pairwise comparism of stormwater runoff against rainfall intensity and terrain pattern using multi criteria evaluation. The result for the research and findings shows that the simulated sub catchments runoff in port harcourt metropolis whereby four catchments were used for the runoff generation, it is vividly shown that the total precipitation in each of the sub catchments is similar which was 1.57 inches while the total infiltration read 0.79 inches, the total runoff was 0.74 inches and 0.08x 106 gallon. Based on the findings, the study recommends that better planning of the city is required to manage the problem of stormwater through various engineering projects. The recommendations are as follow: Implement the port harcourt City Master Plan to guide, monitor, control and manage the areas designated as urban lands to achieve sustainable urban growth and development; [2] as a state policy and urgency, Storm Water Management Framework should be prepared for the city having Storm Water Master Plan to control, manage and monitor storm water – Model for Urban Stormwater Improvement Conceptualisation (MUSIC), 2002 Approach, Structural (engineering methods) and Non-structural (regulations and standards) Storm Water Management approaches should be employed to control and manage flooding challenges in the city
Keywords: GIS; Stormwater; Urban; Catchment